(untitled) (Journal of Educational Sciences, 2018)
Being mobile for a domestic university teacher means to be able to manage own educational activities, build own individual track while clearly pursuing specific goals, forecast own professional activity taking into account the demands laid down by modern society, ability to respond quickly to changes and align own professional pathway with them. Consequently, academic mobility is considered as the ability and aspiration of a person for continuous education and self-education. The definition of “academic mobility” is constantly evolving, new meanings are being put in it. Nevertheless, the significance of the concept remains unchanged. This article, based on comparative analysis of the development of academic mobility abroad and in Kazakhstan, addresses the issues of academic mobility arrangement and development among teachers. Key words: academic mobility, Bologna process, higher education, vertical and horizontal academic mobility, external and internal academic mobility, faculty.